Back to the St. Petersburg Paradox? - Blavatskyy, Pavlo R. (Management Science, 2005)
The conventional parameterizations of cumulative prospect theory do not explain the St. Petersburg paradox. To do so, the power coefficient of an individual’s utility function must be lower than the power coefficient of an individual’s probability weighting function.